Again about "boat check" - Kleshnev, V. (Rowing Biomechanics Newsletter, 2016)
The "check" on a boat at catch is still mentioned as an indicator of rowing technique (e.g., Rowing&Regatta #93 p.60), though advantages of the deeper negative peak of the boat acceleration were proved a number of times (RBN 2012/11, 2016/01). Again, this case study illustrates the positive effect of a more significant "boat check". Two single scullers performed a step-test with the BioRow system, the fastest samples were analysed, both at the stroke rate 37.9/min.